Educational Problems for the Ta'a Tribe Indigenous People in North Morowali Regency, Central Sulawesi Province - Putra, Sepryanus; Tobondo, Yuyun Alfasius; Tondowala, Irsan Bertinus; Sigilipu, Fries Pileman Soa'e (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
Remote indigenous peoples are scattered in various parts of the world. Even though they live far away and isolated from other communities, they also have the same right to education. Based on the author's observations, there are still people who have not received education in the indigenous people of the Ta'a tribe in North Morowali Regency, Central Sulawesi Province. This study aims to find educational problems that occur in isolated tribes. This research was conducted using a qualitative descriptive method, in which researchers collected data through literature studies involving various information from scientific articles and international journals. The results showed that there were three problems in the education of the Ta'a indigenous people in North Morowali Regency, Central Sulawesi Province, the first was the presence of a binding culture, the second was government policy, and the third was low support from parents.